Activation of protease-activated receptor 2 induces VEGF independently of HIF-1. - Jeppe Grøndahl Rasmussen (Public Library of Science (PLoS), 2012)
Background Human adipose stem cells (hASCs) can promote angiogenesis through secretion of proangiogenic factors such as vascular endothelial growth factor (VEGF). In other cell types, it has been shown that induction of VEGF is mediated by both protease activated receptor 2 (PAR2) and hypoxia inducible factor 1(HIF-1). The present study hypothesized that PAR2 stimulation through activation of kinase signaling cascades lead to induction of HIF-1 and secretion of VEGF. Methodology/principal findings Immunohistochemistry revealed the expression of PAR2 receptors on the surface of hASCs. Blocking the PAR2 receptors with a specific antibody prior to trypsin treatment showed these receptors are involved in trypsin-evoked increase in VEGF secretion from hASCs. Blocking with specific kinase inhibitors suggested that that activation of MEK/ERK and PI3-kinase/Akt pathways are involved in trypsin-eveoked induction of VEGF. The effect of the trypsin treatment on the transcription of VEGF peaked at 6 hours after the treatment and was comparable to the activation observed after keeping hASCs for 24 hours at 1% oxygen. In contrast to hypoxia, trypsin alone failed to induce HIF-1 measured with ELISA, while the combination of trypsin and hypoxia had an additive effect on both VEGF transcription and secretion, results which were confirmed by Western blot. Conclusion In hASCs trypsin and hypoxia induce VEGF expression through separate pathways.